Respuesta :

Answer:

  x = 0 and x = 4

Step-by-step explanation:

The two terms on the right have x as a common factor, so the function can be factored as ...

  y = x(x -4)

The zeros are the values of x that make y = 0, so we want the solutions to ...

  0 = x(x -4)

The Zero Product Rule tells us that a product will be zero if and only if at least one factor is zero. Here, the factors are x and (x-4). They are zero when ...

  x = 0   or   x = 4  . . . . . the zeros of the function

ACCESS MORE